2022
DOI: 10.1007/s00359-021-01529-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic maps in animal navigation

Abstract: In addition to providing animals with a source of directional or ‘compass’ information, Earth’s magnetic field also provides a potential source of positional or ‘map’ information that animals might exploit to assess location. In less than a generation, the idea that animals use Earth’s magnetic field as a kind of map has gone from a contentious hypothesis to a well-established tenet of animal navigation. Diverse animals ranging from lobsters to birds are now known to use magnetic positional information for a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 139 publications
0
37
0
Order By: Relevance
“…Sensing the Earth s magnetic field is a widespread ability in the animal kingdom. Behavioral experiments and analyses of data from wild animals have shown that nightmigratory songbirds, fish, amphibians, reptiles and insects orientate and navigate using magnetic sensing [1][2][3][4][5]. Birds sense the inclination of the magnetic field by a process that involves the absorbance of blue light, indicating the involvement of a photoreceptor protein [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Sensing the Earth s magnetic field is a widespread ability in the animal kingdom. Behavioral experiments and analyses of data from wild animals have shown that nightmigratory songbirds, fish, amphibians, reptiles and insects orientate and navigate using magnetic sensing [1][2][3][4][5]. Birds sense the inclination of the magnetic field by a process that involves the absorbance of blue light, indicating the involvement of a photoreceptor protein [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to a clock-and-compass migratory orientation program, it has been proposed that naïve migrants might be able to perform navigation by following gradients in the geomagnetic field (4,28). However, this would result either tend to produce nearly N-S routes following large-scale inclination or intensity gradients, or else involve interpolation between often nearly-parallel inclination and intensity gradients (27,86).…”
Section: Discussionmentioning
confidence: 99%
“…Many airborne migration routes can be largely explained by one or more compass courses (9,10), contingent upon possessing sufficient compass precision (11)(12)(13) and ability to negotiate currents (14,15). However, many migration routes require distinct direction changes (often termed "Zugknicks" for bird migration), e.g., to avoid regions with unfavourable habitats (16)(17)(18), or to exploit favourable habitat (19,20) or supportive current systems (4,21). Mediating such direction changes solely according to a circannual clock is likely unreliable given unpredictable variation in migratory schedules (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations